2020
DOI: 10.1101/2020.12.10.20244509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short of Breath for the Long Haul: Diaphragm Muscle Dysfunction in Survivors of Severe COVID-19 as Determined by Neuromuscular Ultrasound

Abstract: Many survivors from severe coronavirus disease 2019 (COVID-19) suffer from persistent dyspnea and fatigue long after resolution of the active infection. In a cohort of 25 consecutive COVID-19 survivors admitted to an inpatient rehabilitation hospital (76% male), 80% of them had at least one sonographic abnormality of diaphragm muscle structure or function.Specifically, when compared to established normative data, 76% had reduced diaphragm thickening ratio (impaired contractility), and 20% patients had reduced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…Respiratory muscle weakness of unknown aetiology has also been reported in COVID-19 patients (Farr et al, 2020), which might offer an explanation for abnormal lung volumes observed in our cohort (Hart et al, 2002). Consistent with previous accounts demonstrating abnormal lung volumes in individuals recovering from moderateto-critical COVID-19 (Ekbom et al, 2021;González et al, 2021;Huang et al, 2021;Smet et al, 2021), we observed FRC, TLC, VC and RV that were below clinically relevant thresholds in several of our participants recovering from mild-to-moderate illness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Respiratory muscle weakness of unknown aetiology has also been reported in COVID-19 patients (Farr et al, 2020), which might offer an explanation for abnormal lung volumes observed in our cohort (Hart et al, 2002). Consistent with previous accounts demonstrating abnormal lung volumes in individuals recovering from moderateto-critical COVID-19 (Ekbom et al, 2021;González et al, 2021;Huang et al, 2021;Smet et al, 2021), we observed FRC, TLC, VC and RV that were below clinically relevant thresholds in several of our participants recovering from mild-to-moderate illness.…”
Section: Discussionsupporting
confidence: 91%
“…However, the proportion of SARS‐CoV‐2 participants demonstrating abnormal lung volumes in our study was lower than that found in accounts including hospitalized cases of greater severity (Ekbom et al., 2021 ; González et al., 2021 ; Huang et al., 2021 ; Smet et al., 2021 ). Further examination of the mechanisms underlying reduced lung volumes (i.e., fibrotic/inflammatory changes to the pulmonary interstitium, respiratory muscle weakness attributed to neuromuscular manifestations of the virus, and microcirculatory changes leading to atrophy of type II myofibres; Farr et al., 2020 ), via diagnostic imaging and/or tests of respiratory muscle strength, is needed in individuals experiencing post‐acute COVID‐19 syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Postacute sequelae of COVID-19 (PASC) affect up to two out of three of patients, up to 60% of which describe persistent dyspnoea more than 60 days after infection. 5 Here, we describe a case of COVID-19-related unilateral diaphragmatic paralysis causing PASC dyspnoea.…”
Section: Introductionmentioning
confidence: 94%
“…A preprint describing a cohort of 25 patients with COVID-19 treated with mechanical ventilation identified a high burden of diaphragmatic abnormalities. 5 Another study describes 1527 patients with COVID-19, 1.5% of which were diagnosed with diaphragmatic dysfunction on CT scan. 17 These reports differ from ours as each patient was treated with CPAP or mechanical ventilation, both known risk factors for the development of diaphragmatic dysfunction, while our patient received no non-invasiveventilation or mechanical ventilation.…”
Section: Case Reportmentioning
confidence: 99%
“…Comienzan a aparecer un goteo de teorías que justifican el daño residual neurológico o de otros órganos diana, que necesitarán ratificación [19][20][21].…”
Section: ¿Cuáles Son Las Más Importantes Manifestaciones Respiratorias?unclassified